The Mechanical Properties of Drosophila Jump Muscle Expressing Wild-Type and Embryonic Myosin Isoforms - Eldred, Catherine C. (The Biophysical Society, 2010)
Transgenic Drosophila are highly useful for structure-function studies of muscle proteins. However, our ability to mechanically analyze transgenically expressed mutant proteins in Drosophila muscles has been limited to the skinned indirect flight muscle preparation. We have developed a new muscle preparation using the Drosophila tergal depressor of the trochanter (TDT or jump) muscle that increases our experimental repertoire to include maximum shortening velocity (V(slack)), force-velocity curves and steady-state power generation; experiments not possible using indirect flight muscle fibers. When transgenically expressing its wild-type myosin isoform (Tr-WT) the TDT is equivalent to a very fast vertebrate muscle. TDT has a V(slack) equal to 6.1 ± 0.3 ML/s at 15°C, a steep tension-pCa curve, isometric tension of 37 ± 3 mN/mm(2), and maximum power production at 26% of isometric tension. Transgenically expressing an embryonic myosin isoform in the TDT muscle increased isometric tension 1.4-fold, but decreased V(slack) 50% resulting in no significant difference in maximum power production compared to Tr-WT. Drosophila expressing embryonic myosin jumped <50% as far as Tr-WT that, along with comparisons to frog jump muscle studies, suggests fast muscle shortening velocity is relatively more important than high tension generation for Drosophila jumping.